Keka - Viva Films ([Pasig City] Viva Films, 2003)
Keka is the story of a beautiful young woman named Keka (Katya Santos) working in a call center. Wanting to avenge her boyfriend's death five years ago, Keka undergoes rigid training and hunts down the killers. Everything has been going well until she meets Jason Sanchez (Wendell Ramos), a detective who decides to immerse himself in work after his girlfriend rejected his marriage proposal. They meet and eventually fall in love. But when clues about recent murders lead to Keka, conflict arises.
DVD
Executive producer, Vic Del Rosario, Jr. ; written and directed by Quark Henares
Katya Santos, Wendell Ramos, Vhong Navarro, Bobby Andrews, Ryan Eigenmann, Mark Lopez
Keywords: Detective and mystery stories; Feature films